Partial Least Squares Regression Methods with Application of Mas Cement Factory in Sulaymaniyah Governorate - mohyaldeen, Sherin; Alhassawy, Mohammed (Humanities Journal of University of Zakho, 2022)
This paper was dealing with variables for MAS Cement Factory where evince many problems , more than one variable dependent and presence the problem of multicollinearity and so presence the correlation between the predictive variables and the dependent variables and so smallness size the research sample. used the method , Partial Least Squares PLS to Solve the problems above, also considered as one of the methods which dally methodically different in deduction the Components dependent on curing the correlation the presence between the predictive variables and the dependent variables , more over this method is more competence in dealing with the problems above. Through the statistical analysis, the PLS method it has succeeded in establishing the optimal Regression model for all three depended variables for the data of this paper.